The Household Food Security and Stunting of Under-Five Children in Indonesia: A Systematic Review - Dewi, Puspita; Khomsan, Ali; Cesilia Meti Dwiriani (Universitas Airlangga, 2024)
Inadequate access to food at home contributes to growth retardation in childhood. Under-five children who suffer from stunting have problems in their growth and development owing to a lack of nutrients over an extended period of time. This study aimed to analyzed the relationship between household food security and stunting prevalence. This study uses a systematic review using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Seven electronic databases are used: PubMed, ProQuest, MDPI, Science Direct, Scopus, Google Scholar, and Portal Garuda. This research was based on studies conducted in Indonesia and published between 2013 and 2023. For the final result, sixteen articles were included. Household food security has a positive correlation with the stunting of under-five children in Indonesia. Moreover, households with food insecurity had a greater risk of stunting. A household is said to be food-secure when access to food is fulfilled by all family members. From this systematic review, the government is expected to formulate policies and strategies to improve household food security and the nutritional status of children under the age of five. To accomplish these efforts, coordination between sectors is required to accelerate and strengthen the implementation of these policies and strategies.